Supporting Local Bond Market Development : How Can Development Banks Foster Domestic Capital Markets? - Molders, Florian (International Finance Corporation, Washington, DC, 2018)
Domestic capital markets are a vital source of stable, sustainable finance, and underpin a private sector associated with employment and economic growth. Yet capital markets are underdeveloped across the emerging-market world, leading to illiquidity, elevated transaction costs, and other inefficiencies. Development banks can help foster stronger capital markets through local bond issuances, partial credit guarantees, anchor investments, risk sharing, and securitization assistance.